Case reports of one-lung ventilation using Fuji Uniblocker bronchial blockers for infants under one-year-old in uniportal video-assisted thoracoscopic surgery. Issue 27 (9th July 2021) - Chang, Szu-Ling; Lai, Chih-Hung; Chen, Guan-Yu; Chou, Chia-Man; Huang, Sheng-Yang; Chen, Yung-Ming; Liu, Tsun-Jui; Lai, Hui-Chin
Abstract: Introduction: Uniportal video-assisted thoracoscopic surgery (VATS) for various pulmonary diseases provides advantages of less postoperative pain and earlier post-operative recovery over traditional open surgery. The inherent limitation of this surgical modality in manipulation of surgical instruments renders intra-operative one-lung ventilation a requisite to increase the substantially restricted working space and thus visibility of the surgical filed. Patient concerns: Patient 1, an 8-month-old, 9-kg, and 70 cm-in-height male infant was diagnosed as congenital pulmonary airway malformation (CPAM) over left lower lobe. Patient 2, a 9-month-old, 8-kg and 72 cm-in-height male infant was diagnosed as CPAM over right lower lobe. Patient 3, an 8-month-old, 8-kg and 67 cm-in-height female infant was diagnosed as CPAM over left lower lobe. This facilitating one-lung ventilation yet was rarely conducted in infants under one year of age for the extremely small body size, the unavailability of dedicated tools, and therein the very tough techniques demanded. Diagnosis: Infants with congenital cystic adenomatoid malformation Interventions: Here we report three infants of less than one year of age in whom one-lung ventilation was successfully achieved by intraluminal use of 5-Fr Fuji Uniblocker Bronchial Blocker devices and in turn assisted the completion of uniportal VATS for congenital cystic adenomatoid malformation in unilateral lungs. Outcomes: Three infants received VATS under uniblocker smoothly. Patient 1 had two episode of balloon dislodgement and desaturation and solved by re-insertion. And he had subglottic tracheal stenosis which treatment with laser coagulation. Patient 2 had overall blood loss 80 ml. Patient 3 had one episode of desaturation after stapling the bronchus and fiberoptic bronchoscope revealed obstruction by blood and secretion which solved by suction. Conclusion: In conclusion, OLV in infants undergoing uniportal VATs could be successfully achieved by Fuji 5 Fr Uniblocker bronchial blockers for as long as 4 hours, as exemplified by our three cases, and balloon poor sealing and dislodgment can be immediately solved by bronchoscope-guided re-positioning without compromising surgical proceeding or outcome.